Endocrine Changes in Harbor Seal (Phoca vitulina) Pups Undergoing Rehabilitation. Issue 2 (25th July 2012) - Trumble, Stephen J.; O'Neil, Danielle; Cornick, Leslie A.; Gulland, Frances M. D.; Castellini, Michael A.; Atkinson, Shannon
<x xml:space="preserve">Abstract</x> Rehabilitating pinniped pups are often admitted to care centers as neonates and generally lack maternal investment and are in poor body condition. Upon admittance to a rehabilitation facility, pups are typically fed a milk replacement formula via gavage, which is switched to frozen fish upon weaning. While rehabilitation has been successful in terms of recovery and release, preweaning growth rates in captivity are consistently lower than in the wild. Indicators of stress (cortisol and total thyroxine; TT4), and standard morphometrics, of harbor seal pups in rehabilitation (n = 20) were determined for both preweaned and weaned pups. Hormone concentrations and standard morphometrics from pups in care were compared with free‐ranging harbor seal pups (n = 59). Pups in rehabilitation gained mass on both milk and fish diets. Preweaned pups had greater mean serum cortisol and similar TT4 concentrations than weaned pups. Free‐ranging harbor seal pups were heavier and longer than preweaned and weaned pups in rehabilitation. The free‐ranging pups had the lowest cortisol and highest TT4 concentrations of any of the pups. These results suggest that weaned pups that have undergone rehabilitation are not physiologically equivalent to free‐ranging weaned pups. Additional research is needed regarding physiological changes in endocrine values during early development under captive care conditions. This information should be useful to marine mammal rehabilitation centers in their development of care protocols and release criteria for rehabilitating harbor seal pups. Zoo Biol. 32:134–141, 2013. © 2012 Wiley Periodicals, Inc.